HUBUNGAN PERSONAL HYGIENE DENGAN KEJADIAN KEPUTIHAN PADA REMAJA PEREMPUAN - Dini Erlisa Adhani; Dwi Agustin; Melinda Asturia; Wahyudi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Vaginal discharge is a common problem in adolescent girls and can be influenced by various factors, including personal hygiene practices. Daily hygiene practices, such as vulvar cleaning, bathing frequency, underwear selection, and sanitary pad use, play a role in preventing infection and maintaining reproductive health. Although numerous studies have discussed vaginal discharge and its risk factors in general, the specific relationship between personal hygiene and the occurrence of vaginal discharge in adolescent girls still requires specific review.  to determine the relationship between personal hygiene and the incidence of vaginal discharge in adolescent girls This article uses a literature review method by examining various national and international journals, reports from the WHO, CDC, and BKKBN, and related research. The literature was selected based on its recency (last 5 years), relevance, and publisher credibility. Searches were conducted through Google Scholar, PubMed, and DOAJ databases using the keywords "vaginal discharge," "personal hygiene," and "adolescent girls." Data were analyzed descriptively to understand the relationship between personal hygiene and vaginal discharge Based on the literature review, there is a relationship between personal hygiene and the incidence of vaginal discharge in adolescent girls. Good personal hygiene is associated with a lower risk of vaginal discharge, while inadequate hygiene increases the incidence. ducation regarding personal hygiene needs to be improved to prevent vaginal discharge and support reproductive health in adolescent girls.